Prevalence of smoking among male secondary school students in Arar City, Saudi Arabia - Albangy, Fahed Hlilan (Pan Afr Med J, 2019)
INTRODUCTION: Tobacco is one of the leading preventable cause of death worldwide. Tobacco consumption among teenagers is a major public health problem, especially in developing countries. Younger smokers are more liable to smoking complications. The objectives were to evaluate the prevalence of smoking among male secondary school students in the Northern Borders region, KSA. METHODS: A cross-sectional study was conducted in Arar city. Four schools were chosen randomly from 21 secondary schools. A total of 240 students responded to the pre-designed questionnaire. The questionnaire included questions on demographic factors, smoking behavior and knowledge about smoking hazards. RESULTS: Prevalence of current smoking among male secondary school students is 40.8%. Cigarette smoking was the most common type (67.3%) followed by Shish smoking (22.4%). Few students (2.1%) reported other forms of smoking, example (Hashish). Of the studied group, 39.8% smoke on a daily basis with 29.6% of them smoke more than five cigarettes per day. CONCLUSION: Smoking is a prevalent habit among teenagers. Special concern should be directed to smoking cessation campaigns with behavioral, legal and economic interventions.